Prevalence of over-the-counter drug abuse among adults in Jeddah, Saudi Arabia - Safdar, Osama Yousif; Albaz, Ghaidaa Faisal; Mannan, Sara Mohammed; Alshehri, Wejdan Ali; Altumaihi, Razan Mohammed; Bakhashwain, Walaa Jamal; Khayyat, Shahad Tariq; Almehmadi, Wasayf Mohammed (Journal of Contemporary Medical Sciences, 2021)
Objectives: This study aimed to evaluate the prevalence of over-the-counter drug abuse among an adult population in Jeddah, Saudi Arabia. Methods: This was a cross-sectional study, and a validated electronic self-administered questionnaire was administered to the general population in Jeddah, Saudi Arabia, from June to August, 2020. Results: Overall, 400 participants were included in this study. The majority (94%) reported the use of over-the-counter drugs, of which 15.2% reported drug-related problems following over-the-counter drug use. The most frequently preferred over-the-counter drug group was analgesics/antipyretics (90.4%). More than three-quarters of our study participants stated that they read the instructions provided in the leaflet accompanying their medications carefully before use (76.3%). Conclusion: We found a highly significant prevalence of over-the-counter medication use, which exceeded 50%, without any significant association between over-the-counter use and other factors, except for the presence of chronic diseases. We recommend that, the Ministry of Health, Kingdom of Saudi Arabia should play a major role in monitoring the practice of self-medication by implementing policies and creating surveillance committees to that effect.